Crisis del sistema mundo y el fenómeno de la migración transnacional “sur norte” - Valencia León, Ivonne Teresa (2019)
The world is in crisis. Crisis is a term that accounts for some difficulty in the countries’ social dynamics. For this reason, the idea of the World-System crisis is set out to explain all the social variations, which emerge from situations that can’t be resolved until other exogenous factors intervene. Why this crisis occurs? and what does crisis consist of? The latter can be economic (currency devaluation, rising fuel prices, unemployment, low remunerations), political (international blockades, distrust in political parties and breakdowns of democracies), ethical (anti-values, anomie and corruption) and ecological (natural disasters due to climate change and environmental displacement); these are aspects which, in the following paper, are going to be analyzed in relative to one of the major problems nowadays: the transnational migration phenomenon. Consequently, our aim is to study the direct relationship between the current World-System crisis and the transnational migration phenomenon “south-north”. In the next pages, we examine the World-System crisis problem, then we analyze the crisis effects on migration and, lastly, we reflect on the relationship between the crisis and the phenomenon of migration. For that, we analyze Immanuel Wallerstein’s and Aníbal Quijano’s contributions about the World-System crisis and the modern Eurocentric colonial power pattern crisis. We consider the last theoretical proposals for being the ones with the greatest repercussion in the world. In addition, we examine César Germaná’s and Alain Touraine’s contributions on the issue of crisis. Finally, for the subject of chaos we collect some contributions from George Balandier and Ilya Priogogine.